Application of Molecular Sieves for Drying Transformers Insulated with Mineral Oil, Natural Ester, or Synthetic Ester - Mateusz Cybulski; Piotr Przybylek (Energies, 2021)
A high level of moisture in the insulation system of power transformers is often the cause of their failure. This can be prevented by drying a transformer in its place of installation. In the article the application of molecular sieves (MS) in the drying process of the transformer insulation system was analyzed. The water sorption isotherms of 3A MS in mineral oil, natural ester, and synthetic ester at 35 °C were determined, which was not described in the literature before. An evaluation of the influence of temperature on the drying dynamics of electro-insulating liquids using MS was also carried out. The drying dynamics were tested at three temperatures, i.e., 35 °C, 50 °C, and 65 °C, which allowed to analyze the effect of temperature on a short-term or continuous drying process. The tests showed that 3A MS’s ability to adsorb water varied depending on the type of electro-insulating liquid. The determined water sorption isotherms, described by means of Langmuir adsorption model, make it possible to calculate the amount of MS needed for drying transformers with different liquid insulation. The research and analyses show the MS’s great potential for the drying of transformer insulation systems.